St. Mary’s College, Port of Spain - (:unkn) unknown (My University, 2010)
Exterior view of the St. Mary’s College in Port of Spain, Trinidad. This is a secondary school that admits male students only.
Colour; Black and White; Style: Landscape; Other: Bordered, Divided.
Keywords: Trinidad and Tobago; Postcards; St. Mary’s College; Schools